Integritas Sistem Informasi Manajemen Pada Industri Berbasis Komunitas Lokal Di Era Digitalisasi - Septia Amelia; Muhammad Irwan Padli Nasution (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study is to investigate the integrity of the information management system (SIM) in local community-based industries in the digital age. As the use of digital technology increases, local industry is impacted by new opportunities and challenges in information processing. This study employs a deskriptif kualitatif approach, gathering data through observation, document analysis, and fieldwork in a few local communities that use SIM. The study's findings indicate that factors such as effective communication, human safety, and technological infrastructure have a significant impact on SIM integrity. Even while digital technology can increase productivity and efficiency, there are still issues with how members of the community understand and use it. In addition, the main focus is on issues related to data security and accessibility. This study emphasizes the importance of education for community members and the development of policies that support technology use in a responsible manner.